La playa de los ahogados - Villar, Domingo; Villar, Domingo (Madrid : Ediciones Siruela, 2010)
One misty autumn dawn, in a quiet fishing port in northwest Spain, the body of a sailor washes up in the harbor. Detective Inspector Leo Caldas is called in from police headquarters in the nearby city of Vigo to sign off on what appears to be a suicide; but details soon come to light that turn this routine matter into a complex murder investigation. Finding out the truth is not easy when the villagers are so suspicious of outsiders. As Caldas delves into the maritime life of the village, he uncovers a disturbing decade-old case of a shipwreck and two mysterious disappearances. This chilling story of violence, blackmail, and revenge has enthralled readers across Europe.
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Caldas, Leo -- (Ficitious character) -- Fiction; Police -- Spain -- Galicia (Region) -- Fiction; Sailors -- Crimes against -- Spain -- Galicia (Region) -- Fiction; Detective and mystery fiction; Electronic books